2013
DOI: 10.1016/j.celrep.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of DROSHA and DGCR8 by Expanded CGG RNA Repeats Alters MicroRNA Processing in Fragile X-Associated Tremor/Ataxia Syndrome

Abstract: SUMMARY Fragile X-associated tremor/ataxia syndrome (FXTAS) is an inherited neurodegenerative disorder caused by the expansion of 55–200 CGG repeats in the 5′ UTR of FMR1. These expanded CGG repeats are transcribed and accumulate in nuclear RNA aggregates that sequester one or more RNA-binding proteins, thus impairing their functions. Here, we have identified that the double-stranded RNA-binding protein DGCR8 binds to expanded CGG repeats, resulting in the partial sequestration of DGCR8 and its partner, DROSHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
247
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 223 publications
(256 citation statements)
references
References 50 publications
(82 reference statements)
6
247
0
3
Order By: Relevance
“…Lin28A/B enhances the growth of breast and colon tumors via inhibition of let-7 miRNA biogenesis (25). Fragile X-associated tremor/ataxia syndrome, a neurodegenerative disorder, is caused by the expansion of 55 to 200 CGG repeats in the 5= untranslated region of FMR1 that inhibits Drosha-mediated pri-miRNA processing through binding of the Drosha-DGCR8 complex to CGG repeats (53). Cardiac dysfunction in type I myotonic dystrophy is implicated in the reduction of miR-1 processing caused by the fall in the activity of MBNL1 as a positive regulator of processing from premiR-1 to miR-1 (54).…”
Section: Discussionmentioning
confidence: 99%
“…Lin28A/B enhances the growth of breast and colon tumors via inhibition of let-7 miRNA biogenesis (25). Fragile X-associated tremor/ataxia syndrome, a neurodegenerative disorder, is caused by the expansion of 55 to 200 CGG repeats in the 5= untranslated region of FMR1 that inhibits Drosha-mediated pri-miRNA processing through binding of the Drosha-DGCR8 complex to CGG repeats (53). Cardiac dysfunction in type I myotonic dystrophy is implicated in the reduction of miR-1 processing caused by the fall in the activity of MBNL1 as a positive regulator of processing from premiR-1 to miR-1 (54).…”
Section: Discussionmentioning
confidence: 99%
“…FXTAS and FXPOI are seen in the carriers of FMR1 premutation (PM) alleles that have 55-200 CGG-repeats. The clinical symptoms of those with FXTAS and FXPOI are thought to arise primarily from some deleterious consequence of the expression of the PM allele [26][27][28][29]. However, PM carriers often have symptoms that are reminiscent of those seen in FXS.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the death of granulosa cells and perhaps oocytes themselves in POI and POF can recognize, as a pathogenic mechanism, a dynamic intracellular accumulation of cytotoxic amounts of aggregated CGG repeats that in turn sequester proteins like DROSHA and Sam68 [83]. The final result will be the interference with some important cellular functions.…”
Section: Fmr1 Gene Mutations and Reproductive Agingmentioning
confidence: 99%